2023
DOI: 10.3390/antiox12030574
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Inflammatory Properties of Phytochemicals Found in the Yucca Genus

Abstract: The Yucca genus encompasses about 50 species native to North America. Species within the Yucca genus have been used in traditional medicine to treat pathologies related to inflammation. Despite its historical use and the popular notion of its antioxidant and anti-inflammatory properties, there is a limited amount of research on this genus. To better understand these properties, this work aimed to analyze phytochemical composition through documentary research. This will provide a better understanding of the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 241 publications
0
5
0
Order By: Relevance
“…Activation of TLR4 results in the dissociation of NF-κB from IκBα, thereby promoting inflammation [ 49 ]. The predominant form of NF-κB is the p65:p50 heterodimer, and the activation of p65 is pivotal in the pathogenesis of numerous chronic diseases, including dermatitis-like conditions, inflammatory bowel disease, multiple sclerosis, and neurodegenerative disorders [ 50 ]. Consequently, the NF-κB p65 signaling pathway has become a focal point in drug discovery and development initiatives [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Activation of TLR4 results in the dissociation of NF-κB from IκBα, thereby promoting inflammation [ 49 ]. The predominant form of NF-κB is the p65:p50 heterodimer, and the activation of p65 is pivotal in the pathogenesis of numerous chronic diseases, including dermatitis-like conditions, inflammatory bowel disease, multiple sclerosis, and neurodegenerative disorders [ 50 ]. Consequently, the NF-κB p65 signaling pathway has become a focal point in drug discovery and development initiatives [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Naringenin may mitigate these secondary injury factors through its anti-inflammatory, antioxidant, and anti-apoptotic properties. Naringenin reduced hippocampal expression of proinflammatory cytokines, including TNF-α, IL-1β, and IL-6, in a controlled cortical impact model of TBI in mice ( Culhuac et al, 2023 ). This anti-neuroinflammatory effect was accompanied by attenuated neuronal apoptosis, edema, and improved cognitive function.…”
Section: Role Of Phytochemicals In Tbimentioning
confidence: 99%
“…In order to conduct preliminary investigations on the ability of the aforementioned gold nanoparticles on their propensity to target M2-like protumor macrophage cell lines, we have chosen RAW 264.7 macrophage cell lines. 26,27 RAW 264.7, by default, manifests M2-like protumor characteristics within the tumor microenvironment and is directly involved in the growth, propagation, and metastases of most human/mammalian tumors. 26 As shown in Figure 16, a significant difference in cellular density between cancer cells treated with naïve macrophage cell lines and those treated with YF-AuNPs pretreated macrophage cell lines.…”
Section: Targeting Of M2-like Protumor Macrophage Cell Lines By Yf-au...mentioning
confidence: 99%
“…Historically, the Yucca genus has been used by indigenous Cherokee and the Catawba Indians in folk medicine to treat joint pain, asthma, bleeding, rheumatism, gonorrhea, sunburns, arthritis, prostate, and urethral inflammations. 27 Adegbeye et al 28 reported on the importance of Yucca extract as feed additives because their phytochemicals can reduce methane by 8%-69%, total ammonia nitrogen in water by 50%-100%, nitrous oxide emissions by 75% while reducing nutrient digestibility and thereby reducing livestock environmental footprint. Yucca products have found utility as animal feed additives, food supplements, para-pharmaceutical complements, foaming agent in beverages, moisturizing agents, and as crop growth stimulants.…”
Section: Introductionmentioning
confidence: 99%